Penentuan Konduktivitas Listrik dan Frekuensi Karakteristik Sel Ragi dengan Memanfaatkan Proses Dielektroforesis - Much Azam; Wahyu Setia Budi; Hermin Pancasakti (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2010)
Dielectrophorestic (DEP), a phenomenon where small particles such as yeast cells are manipulated by non-uniform electric fields. The net dielectrophoretic force is proportional to the polarisability of the cell and cause this cell moving toward higher field. By measuring velocity of the cell on the various frequency of the electric field, it can determine the electrical conductivity and the characteristic frequency of the yeast cells. The results showed that the conductivity of the yeast cell was (10,0 ± 0,4)10-9 Sm-1  and the characteristic frequency was 60 kHz.